2016
DOI: 10.1038/srep34525
|View full text |Cite
|
Sign up to set email alerts
|

DNA annealing by Redβ is insufficient for homologous recombination and the additional requirements involve intra- and inter-molecular interactions

Abstract: Single strand annealing proteins (SSAPs) like Redβ initiate homologous recombination by annealing complementary DNA strands. We show that C-terminally truncated Redβ, whilst still able to promote annealing and nucleoprotein filament formation, is unable to mediate homologous recombination. Mutations of the C-terminal domain were evaluated using both single- and double stranded (ss and ds) substrates in recombination assays. Mutations of critical amino acids affected either dsDNA recombination or both ssDNA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 48 publications
(76 reference statements)
2
40
0
Order By: Relevance
“…23 Finally, through crosslinking Redβ to a 36mer oligonucleotide, DNA-binding was localized to a 20 kDa N-terminal domain (NTD). 21 In 2016, 10 years after identification of the NTD of Redβ as the DNA-binding domain, Smith and Bell 24 and Subramaniam et al 25 independently investigated the functional roles of the N and C-terminal domains (CTDs) in detail. Smith and Bell 24 examined the effect of DNA length on the binding affinity for WT and C-terminally truncated (residues 1-177) Redβ.…”
Section: The Overlooked Redβ Enters the Spotlightmentioning
confidence: 99%
See 4 more Smart Citations
“…23 Finally, through crosslinking Redβ to a 36mer oligonucleotide, DNA-binding was localized to a 20 kDa N-terminal domain (NTD). 21 In 2016, 10 years after identification of the NTD of Redβ as the DNA-binding domain, Smith and Bell 24 and Subramaniam et al 25 independently investigated the functional roles of the N and C-terminal domains (CTDs) in detail. Smith and Bell 24 examined the effect of DNA length on the binding affinity for WT and C-terminally truncated (residues 1-177) Redβ.…”
Section: The Overlooked Redβ Enters the Spotlightmentioning
confidence: 99%
“…Attention was then turned to the CTD of Redβ, with circular dichroism spectroscopy experiments by Smith and Bell 24 predicting that residues 182-261 formed a predominantly α-helical fold, which was sufficient to form a stable interaction with λExo. Subramaniam et al 25 reported a K D of 8 μM for the interaction between full-length Redβ and λExo, but also found it was weakened by deletion to the NTD domain, suggesting that the NTD may still have some influence on λExo binding, and hence this point requires further clarification. Both groups then went on to show that while still able to affect annealing, C-terminally truncated Redβ was unable to mediate recombination 24,25 and that the removal of just 11 amino acids from the C-terminus 24 or the introduction of point mutations 25 prevented recombination.…”
Section: The Overlooked Redβ Enters the Spotlightmentioning
confidence: 99%
See 3 more Smart Citations